The welfare we want? : the British challenge for American reform / edited by Robert Walker and Michael Wiseman. - Walker, Robert, 1949-; Wiseman, Michael (Michael L.) (Policy Press, 2003)
The Welfare We Want? presents a detailed and unique comparison of welfare policies in Britain and America. A team of international experts outlines, compares and contrasts the reform strategies pursued in each country and summarises the results to date.